STUDI PERBANDINGAN NILAI UNDRAINED SHEAR STRENGTH TERHADAP NILAI LIQUID LIMIT TANAH LEMPUNG - Angelina, Sherlin; Prihatiningsih, Aniek (JMTS: Jurnal Mitra Teknik Sipil, 2025)
The correlation analysis between undrained shear strength (Su) and liquid limit (LL) was conducted on clay soils sampled from North Jakarta to evaluate the potential for predicting Su values based on LL parameters. Clay soils are known for their high plasticity, which is influenced by moisture content, making Su and LL critical parameters in geotechnical stability analysis. In this research, Su values were obtained using the Triaxial UU method, while LL values were determined using the Casagrande method and the fall cone test. Exponential regression analysis was used to measure the correlation between Su and LL. Results showed that the Casagrande method generated a coefficient of determination (R2) calculated at 0,9676, indicating a strong correlation for predicting Su. In comparison, the fall cone test method produced a lower coefficient of determination, which is 0,5827. These results imply that LL, especially from the Casagrande method, can be used as a preliminary estimate of Su values, allowing for time and cost efficiency by reducing the need for Triaxial UU testing. Further studies with varied samples and mineral analysis of clay soils are recommended to enhance the accuracy and reliability of these findings. Abstrak Analisis korelasi antara undrained shear strength (Su) dan liquid limit (LL) dilakukan pada sampel tanah lempung yang diambil dari Jakarta Utara untuk mengevaluasi potensi prediksi nilai Su berdasarkan parameter LL. Tanah lempung dikenal memiliki karakter plastisitas tinggi yang dipengaruhi oleh kadar air, sehingga parameter Su dan LL sangat penting dalam analisis stabilitas geoteknik. Pada penelitian ini, nilai Su diperoleh menggunakan metode Triaxial UU, sementara nilai LL diperoleh dengan metode Casagrande dan fall cone test. Analisis regresi eksponensial digunakan untuk mengukur korelasi antara Su dan LL. Hasil menunjukkan bahwa metode Casagrande menghasilkan koefisien determinasi (R2) sebesar 0,9676 yang mengindikasikan korelasi kuat untuk memprediksi Su. Sebaliknya, metode fall cone test menghasilkan koefisien determinasi yang lebih rendah, yaitu 0,5827. Hasil ini menyiratkan bahwa LL, terutama dari metode Casagrande, dapat digunakan sebagai estimasi awal nilai Su, sehingga memungkinkan efisiensi waktu dan biaya tanpa melakukan pengujian Triaxial UU. Studi lanjutan dengan variasi sampel dan analisis mineral tanah lempung disarankan untuk memperkuat keakuratan hasil ini.